MISS HAVISHAM’S INSANITY IN CHARLES DICKENS’ GREAT EXPECTATIONS - Boris Candra Widyasana; eko budi setiawan (Humaniora Scientia, 2018)
The research aims to discuss Miss Havisham’s insanity and its effect toward herself and othercharacter in Charles Dickens’ Great Expectations. The objectives of the research are todescribe Miss Havisham’s insanity and figure out the effect of Miss Havisham’s insanitytoward herself and other character, such as Pip and Estella. The theories that are used in thisstudy are character and characterization in order to find out the effect of Miss Havisham’sinsanity toward other characters. While the theories of insanity as Diogenes Syndrome is todescribe the scale of Miss Havisham’s insanity.  The method of this research is said to bedescriptive, and the technique of data collecting used is library research. There are twoapproaches used in the analysis namely psychological and sociological approach. The resultof the research shows Miss Havisham’s insanities based on Diogenes Syndrome are selfneglect,domestic squalor, and social withdrawal. Miss Havisham’s insanity takes effect onherself and making her hate every men and deny her own feeling. Meanwhile, MissHavisham’s insanity also takes effect toward other character, such as Pip and Estella. InEstella, Miss Havisham’s insanity makes her become Miss Havisham’s doll and makes her asa rude woman. In Pip, Miss Havisham’s insanity makes him love Estella and change hisdream from a blacksmith boy into a gentleman. In conclusion, Miss Havisham’s insanity cantake effect toward herself and other character, such as Pip and Estella.